Thanatophoric dysplasia: a case report - Jahan, Uruj; Sharma, Astha; Gupta, Neena; Gupta, Shruti; Usmani, Fatima; Rajput, Ankita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Thanatophoric Dysplasia (TD) is a congenital, sporadic and most lethal skeletal dysplasia caused by new mutation in FGFR3 gene. Authors report such a rare case of a term alive baby with dysmorphic features, born to an unbooked, 40 years old G4P3+0 with non-consanguineous marriage; admitted at 9 months of gestation to present hospital with complain of pain abdomen for 2 days. Patient delivered a term female baby of vaginally which had delayed cry after birth, Admitted in NICU immediately with respiratory distress. The baby looked dysmorphic and suggested TD as most likely diagnosis. The case is being reported for its rarity and for high importance of early booking and anomaly scan. Early diagnosis is important since it provides alternative options of termination of pregnancy when an affected foetus is detected.